Trachoma in Viet Nam: results of 11 surveillance surveys conducted with the Global Trachoma Mapping Project. (28th December 2018) - Hiep, Nguyen Xuan; Ngondi, Jeremiah M.; Anh, Vu Tuan; Dat, Tran Minh; An, Tran Van; Dung, Nguyen Chi; Thang, Nguyen Duy; Chu, Brian K.; Willis, Rebecca; Bakhtiari, Ana; Pavluck, Alexandre L.; Johnson, James; et al.
ABSTRACT: Purpose : Following interventions against trachoma in Viet Nam, impact surveys conducted in 2003–2011 suggested that trachoma was no longer a public health problem. In 2014, we undertook surveillance surveys to estimate prevalence of trachomatous inflammation—follicular (TF) and trichiasis. Methods : A population-based prevalence survey was undertaken in 11 evaluation units (EUs) encompassing 24 districts, using Global Trachoma Mapping Project methods. A two-stage cluster sampling design was used in each EU, whereby 20 clusters and 60 children per cluster were sampled. Consenting eligible participants (children aged 1–9 years and adults aged ≥50 years) were examined for trachoma. Results : A total of 9391 households were surveyed, and 20, 185 participants (98.8% of those enumerated) were examined for trachoma. EU-level TF prevalence in 1–9-year-olds ranged from 0% to 1.6%. In one cluster (in Hà Giang Province), the percentage of children with TF was 10.3%. The overall pattern of cluster-level percentages of children with TF, however, was consistent with an exponential distribution, which would be consistent with trachoma disappearing. Among people aged ≥50 years, prevalence of trichiasis by EU ranged from 0% to 0.75%; these estimates are equivalent to 0–0.13% in all ages. The prevalence of trichiasis unknown to the health system among people aged ≥50 years, by EU, ranged from 0% to 0.17%, which is equivalent to 0–0.03% in all ages. Conclusion : Findings suggest that trachoma is no longer a public health problem in any of the 11 EUs surveyed. However, given the high proportion of children with TF in one cluster in Hà Giang Province, further investigations will be undertaken.